Chitosan-Based Nanoparticles for Intracellular Delivery of ISAV Fusion Protein cDNA into Melanoma Cells: A Path to Develop Oncolytic Anticancer Therapies. (29th April 2020) - Robles-Planells, Claudia; Sánchez-Guerrero, Giselle; Barrera-Avalos, Carlos; Matiacevich, Silvia; Rojo, Leonel E.; Pavez, Jorge; Salas-Huenuleo, Edison; Kogan, Marcelo J.; Escobar, Alejandro; Milla, Luis A.; Fernandez, Ricardo; Imarai, Mónica; et al.
Abstract : Oncolytic virus therapy has been tested against cancer in preclinical models and clinical assays. Current evidence shows that viruses induce cytopathic effects associated with fusogenic protein-mediated syncytium formation and immunogenic cell death of eukaryotic cells. We have previously demonstrated that tumor cell bodies generated from cells expressing the fusogenic protein of the infectious salmon anemia virus (ISAV-F) enhance crosspriming and display prophylactic antitumor activity against melanoma tumors. In this work, we evaluated the effects of the expression of ISAV-F on the B16 melanoma model, both in vitro and in vivo, using chitosan nanoparticles as transfection vehicle. We confirmed that the transfection of B16 tumor cells with chitosan nanoparticles (NP-ISAV) allows the expression of a fusogenically active ISAV-F protein and decreases cell viability because of syncytium formation in vitro . However, the in vivo transfection induces a delay in tumor growth, without inducing changes on the lymphoid populations in the tumor and the spleen. Altogether, our observations show that expression of ISAV fusion protein using chitosan nanoparticles induces cell fusion in melanoma cells and slight antitumor response.